AUTOMATIC WATER PUMP CONTROLLER - BABU, P.MAHESH; KIRAN, K.RAVI; SATHISH, K.; PRIYA, A.HARI; PRADEEP, B. (The journal of contemporary issues in business and government, 2021)
Water is the most important nature’s gift to man kind. Without water there is no life. Now everybody understands its importance , especially where water is not easily available. Now this is being managed by the proper manner in city areas where the use of water is more than its availability.Automatic water pump controller for both overhead and underground tank is designed to monitor the level of water in the tank. It displays the level of the water when it is at the lowest level; a pump is activated automatically de-energized.Several circuits are put together to ensure proper working of this design and the bock diagram includes the supply unit, the microprocessor unit, the sensor unit, and display unit, and the pump drives unit.